Combined study to explore planar-mixed dimensional Cs3Bi2I9 solar cells - Zulhafizhazuan, Wan; Bin Rafiq, Md Khan Sobayel; Shafian, Shafidah; Sepeai, Suhaila; Ibrahim, Mohd Adib (Center of Biomass & Renewable Energy (CBIORE), 2025)
The development of high-efficiency solar cells is of paramount importance for advancing sustainable energy technologies and meeting global energy demands. This study focuses on the optoelectronic performance of FTO/TiO2/Cs3Bi2I9/Spiro-OMeATAD/Ag planar heterojunction solar cells. Through detailed analysis, we investigated various factors such as crystallite size, strain, dislocation density, and their collective influence on the overall performance of the solar cells. Among the fabricated samples, sample A3 exhibited a significant improvement in efficiency, showing a 0.72% enhancement over the others. This increase is attributed to A3's superior crystallite quality, which led to reduced strain and a lower density of dislocations. These properties contribute to minimizing non-radiative recombination losses and enhancing charge carrier mobility, both of which are crucial for maximizing the photovoltaic performance of the device. These factors bring A3 closer to the theoretical Shockley-Queisser (S-Q) efficiency limit, a benchmark for photovoltaic performance. Further analysis using SCAPS-1D simulations supported these experimental findings, demonstrating the significance of optimizing critical parameters such as the minority carrier lifetime. The simulations revealed that high losses in short-circuit current density (JSC) were a primary limiting factor in performance, emphasizing the need for careful tuning of these parameters to reduce losses. This work highlights the critical role of precise material engineering in developing highly efficient perovskite solar cells. The study not only provides insights into the structural and electronic properties essential for performance enhancement but also underscores the potential of Cs3Bi2I9 as a promising material for photovoltaic applications. The findings offer valuable guidance for the next generation of high-efficiency, low-toxicity, and lead-free perovskite solar cells, aligning with global efforts to transition to clean, renewable energy sources.